Parents’ perspectives of the transition to independent living for young adults with autism spectrum disorder / Nik Nadia Nik Nazri - Nik Nadia , Nik Nazri (2022)
Aim: This present study aims to explore parents’ perspectives on the transition to independent living of young adults with ASD in Malaysia, particularly in the domains that define transitioning, namely; social participation, school and work opportunities. Methodology: Semi-structured interviews were conducted with 4 parents of young adults with ASD where they expressed their views and elaborate on the various challenges faced during the period of transitioning for their children related to these domains. Findings: All the parents held the view that the young adults with ASD were not ready for transition to independent living despite being of the age expected to. This is attributed to various factors including lack of public awareness, teachers’ limited knowledge of strategies for dealing with children with ASD, financial limitations to consider other alternatives and the limited number of centres that provide long term support were the issues raised by parents of young adults diagnosed with autism. As for parents of the young adult diagnosed with Asperger’s Syndrome, difficulty in social communication was consistently highlighted. However, they are hopeful for the future if there is an improvement in the awareness among society, schoolteachers and professionals, as well as increased efforts to create a more conducive and supportive school and working environment for your adults with ASD. Limitations: Repeating this study in rural areas and with more participants may increase generalizability of study